2002
DOI: 10.1074/jbc.m106339200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Osteoblast Differentiation Factor RUNX2 (Cbfa1/AML3/Pebp2αA) Is Inhibited by Tumor Necrosis Factor-α

Abstract: The transcription factor RUNX2 (Cbfa1/AML3/Pebp-2␣A) is a critical regulator of osteoblast differentiation. We investigated the effect of the inflammatory cytokine tumor necrosis factor ␣ (TNF) on the expression of RUNX2 because TNF is known to inhibit differentiation of osteoblasts from pluripotent progenitor cells. TNF treatment of fetal calvaria precursor cells or MC3T3-E1 clonal pre-osteoblastic cells caused a dose-dependent suppression of RUNX2 steady state mRNA as measured by reverse transcription-PCR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
325
2
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(346 citation statements)
references
References 50 publications
11
325
2
8
Order By: Relevance
“…Previous studies have identified numerous proteins that either enhance Runx2 function at the post-transcriptional level (13)(14)(15)(16) or modulate Runx2 activity by regulating the expression/ transcription of the Runx2 promoter (61)(62)(63)(64)(65). Our data indicate that additional mechanisms that negatively regulate Runx2 at the post-transcriptional level also exist.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have identified numerous proteins that either enhance Runx2 function at the post-transcriptional level (13)(14)(15)(16) or modulate Runx2 activity by regulating the expression/ transcription of the Runx2 promoter (61)(62)(63)(64)(65). Our data indicate that additional mechanisms that negatively regulate Runx2 at the post-transcriptional level also exist.…”
Section: Discussionmentioning
confidence: 53%
“…(42,43) In a context of high concentration of growth factors and low expression of RUNX2, TNF-a may inhibit osteoblastic differentiation through TNFR1 independently of apoptosis. (42,44) In these conditions, inhibition of proliferation without any effect on apoptosis induced by TNF-a could be explained by the effects of high percent of FCS on RUNX2 level.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions of OCN are poorly understood, gene deletion studies suggest possible functions in bone remodeling (10). The expression of OCN is regulated by a number of calcitropic hormones and growth factors including 1,25-dihydroxy vitamin D 3 (11)(12)(13), glucocorticoids (14,15), PTH (16), bone morphogenetic proteins (17), basic fibroblast growth factor 2 (18), tumor necrosis factor-␣ (19), and transforming growth factor ␤ (20). A number of transcription factors that bind to specific regions of the osteocalcin gene promoter have also been identified.…”
mentioning
confidence: 99%